2023
DOI: 10.1111/josi.12576
|View full text |Cite
|
Sign up to set email alerts
|

A perceived control‐relationally devaluing experiences model of low socioeconomic status vulnerability to negative relationship outcomes

Abstract: We propose that individuals low (vs. high) in socioeconomic status (SES) are vulnerable to impaired relationship functioning through two different mutually reinforcing paths that both directly implicate perceptions of control and relational devaluation. The first of these involves chronic exposure to relational devaluation as a function of factors such as stigmatization in broader society that serves to undermine low SES individuals' perceptions of control. The second involves enhanced reactivity to relational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 406 publications
(460 reference statements)
0
5
0
Order By: Relevance
“…Throughout the research in this special issue, the role of policy in shaping relational outcomes for members of stigmatized groups has been highlighted. Eliminating discriminatory policy, such as marriage bans (Frost & LeBlanc, 2023), prohibitions on gender‐affirming care (Lewis et al., 2023), and forced relocation of people experiencing homelessness (Rea, 2023), as well as introducing policy aimed at remediating social inequalities, such as universal basic income (Petsnik & Vorauer, 2023), multicultural immigration policy (Froehlich et al, 2023), and adequate parental leave (Vink et al., 2023), will be vital to ensuring not only physical and mental health equity, but also equity in social health between members of stigmatized and dominant groups (Doyle & Link, 2022). It is our aim that this special issue points toward a framework for scholars to further push the boundaries in understanding the social consequences of stigma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the research in this special issue, the role of policy in shaping relational outcomes for members of stigmatized groups has been highlighted. Eliminating discriminatory policy, such as marriage bans (Frost & LeBlanc, 2023), prohibitions on gender‐affirming care (Lewis et al., 2023), and forced relocation of people experiencing homelessness (Rea, 2023), as well as introducing policy aimed at remediating social inequalities, such as universal basic income (Petsnik & Vorauer, 2023), multicultural immigration policy (Froehlich et al, 2023), and adequate parental leave (Vink et al., 2023), will be vital to ensuring not only physical and mental health equity, but also equity in social health between members of stigmatized and dominant groups (Doyle & Link, 2022). It is our aim that this special issue points toward a framework for scholars to further push the boundaries in understanding the social consequences of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Another psychological mechanism that links stigma to social relationships is the experience of lack of control. Petsnik and Vorauer (2023) proposed a novel conceptual model of how the stigma associated with lower SES leads to increased reactivity to relationally devaluing experiences, such as discrimination and ostracism, and subsequently poorer relationship functioning. These authors proposed that the life experiences of people lower in SES persuade them that they have little power or control over their outcomes.…”
Section: What Psychosocial Tendencies Do People From Stigmatized Soci...mentioning
confidence: 99%
“…Doyle and Molix (2014) focused on physiological and psychological pathways for the adverse impacts of discrimination on relationship quality and showed that the effect was mediated by increased emotion dysregulation and chronic inflammation. Further psychological pathways may include decreased trust (Zhang et al, 2020), a reduced sense of belonging (Froehlich et al, 2023), or loss of control that can lead to aggression and controlling behavior (Kazmierski et al, 2023; Petsnik & Vorauer, 2023). Furthermore, discrimination can manifest within relationships, for instance in the form of friendly teasing, making discrimination more ambiguous and thus more challenging to cope with (Douglass et al, 2016; Yampolsky et al, 2023).…”
Section: Levels Of Discriminationmentioning
confidence: 99%
“…Further psychological pathways may include decreased trust (Zhang et al, 2020), a reduced sense of belonging (Froehlich et al, 2023), or loss of control that can lead to aggression and controlling behavior (Kazmierski et al, 2023;Petsnik & Vorauer, 2023). Furthermore, discrimination can manifest within relationships, for instance in the form of friendly teasing, making discrimination more ambiguous and thus more challenging to cope with (Douglass et al, 2016;Yampolsky et al, 2023).…”
Section: Physiological Social and Behavioral Pathways Between Stress ...mentioning
confidence: 99%
“…At the same time, while the special issue generated a focus on social relationships it also allowed a broad consideration of many different stigmatizing circumstances. Relationship stigma is considered with respect to gender (Turetsky et al., 2023), low socioeconomic status (Park et al., 2023; Pestnik et al., 2023), mental illness (Ballinger et al., 2023) transgender people (Lewis et al., 2023) racism (Debrosse et al., 2023), same sex couples (Frost & Leblanc, 2023), weight (Schmidt et al., 2023), HIV (Gamarel et al., 2023; Khurshid et al., 2023), immigration status (Froehlich et al., 2023), gay men (Eschliman et al., 2023; Lattanner & Hatzenbuehler, 2023), homelessness (Rea, 2023), and women who earn more than their male partners (Vink et al., 2023). A final paper addressed 23 circumstances to show that mothers who experience stigma report more controlling behaviors with their daughters (Kazmierski et al., 2023.…”
Section: Situating This Special Issue Within the Context Of Prior Con...mentioning
confidence: 99%